Dynamics of Regulatory and Policy Changes in Child Custody in Indonesia and Malaysia: A Comparative Analysis in Responding to Modern Family Issues - Muhammad Azhad Al-Bohari (Journal of Islamic Mubadalah, 2025)
This study discusses the dynamics of child custody policies in Indonesia and Malaysia in the face of modern family challenges, such as divorce, mixed marriages, single-parent families, and the increasingly dominant role of women. Both countries have legal system that combine civil law and religious law, which often create tensions in the implementation of child custody rights. The study analyzez the influence of globalization and international human rights standars, particularly the UN Convention on the rights of the child, on these policies, as well as the challenges in integrating international principles with domestic law. Tha research method used is a literature study with a comparative analisys, gathering data form journal, books, policy document, and relevant online sources regarding child custody regulations in Indonesia and Malaysia. The result show that although both countries have ratified the UN Convention on the Rights of the Child, its implementation still faces obstacles due to differences in legal system and social norms. In Indonesia, religious law is more dominant in determining child custody, while in Malaysia, there is a dual legal system between civil and sharia law. However, there are opportunities to strengthen child custody policies that are more inclusive and responsive to modern families by involving courts, social institutions, and the government. The study concludes that to unsere optimal child protection, both countries need to align their policies with international standars and be more sensitive to the social changes occurring within modern families.